Legal Analysis of the Role and Legal Liability of Actors in Collective Narcotics Crimes: A Study of Decision Number 35/Pid.Sus/2025/PN Mtk - Juandah; Saliman, Abdul Rasyid; Abdillah, Junaidi (GoAcademica Research & Publishing, 2025)
This study aims to analyze the application of law and the form of liability of offenders in collective narcotics crimes as reflected in the District Court Decision of Mentok Number 35/Pid.Sus/2025/PN Mtk. The research method used is normative legal research with a case approach and statutory approach. The primary data are obtained from court decisions and Law Number 35 of 2009 on Narcotics, supported by secondary legal materials such as legal literature and academic journals. The results show that Article 114 paragraph (2) in conjunction with Article 55 paragraph (1) point 1 of the Indonesian Penal Code was applied to prosecute the defendants who collectively committed the illegal distribution of Class I narcotics in the form of 55 kilograms of marijuana. Although the defendants had different levels of involvement, the court imposed heavy collective sentences, reasoning that their participation was active and organized. Nevertheless, the proportionality of sentencing among the defendants remains a legal concern regarding the implementation of the principle of justice in criminal law. This finding emphasizes the importance of assessing the degree of culpability and individual role in determining criminal liability within collective narcotics offenses.